1981
DOI: 10.1111/j.1346-8138.1981.tb02554.x
|View full text |Cite
|
Sign up to set email alerts
|

Geographical Pattern of Pemphigus in North India

Abstract: A clinical analysis of 70 patients suffering from various types of pemphigus is presented. It revealed a characteristic morphology, and occurrence in a relatively younger age group. Sex had hardly any impact on the disease. Pemphigus vulgaris constituted the largest group. Corticosteroids were the mainstay of its treatment although both lower initial and maintenance dosages were needed in our patients in contrast to those of the standard literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

1987
1987
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…9 Similarly, many Indian studies have reported a lower prevalence of oral lesions in PV cases. 12 These ethnographic and genetic factors may probably explain the higher anti-dsg1 positivity and comparatively greater proportion of cutaneous involvement (26 of 27 patients had cutaneous lesions) in our patients.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…9 Similarly, many Indian studies have reported a lower prevalence of oral lesions in PV cases. 12 These ethnographic and genetic factors may probably explain the higher anti-dsg1 positivity and comparatively greater proportion of cutaneous involvement (26 of 27 patients had cutaneous lesions) in our patients.…”
Section: Discussionmentioning
confidence: 67%
“…A study from the UK assessed the influence of race on the frequency of anti‐dsg1 in PV, and showed that 75% of cases from the Indian subcontinent had raised anti‐dsg1, compared with only 46% of patients of north European origin and 57% of patients of other races 9 . Similarly, many Indian studies have reported a lower prevalence of oral lesions in PV cases 12 . These ethnographic and genetic factors may probably explain the higher anti‐dsg1 positivity and comparatively greater proportion of cutaneous involvement (26 of 27 patients had cutaneous lesions) in our patients.…”
Section: Discussionmentioning
confidence: 99%
“…In India, although cases are reported from all regions, most are from the northern, eastern, and western parts, with few from the south, and there is considerable interstate variation. 21 The majority of the population in India is Hindus, and they comprise 63% of our pemphigus patients. Although Sikhs constitute only 2% of the whole Indian population, we observed that 33% of our patients were Sikhs, although the fact that more Sikhs live in Punjab cannot be overlooked.…”
Section: Pemphigus In North Indiamentioning
confidence: 99%
“…In a majority of the cases, the diagnosis of pemphigus vulgaris (PV) and pemphigus foliaceous (PF), the two major variants, rests upon clinical, histological and immunofluorescence features. [1] However, at times, differentiation between these two variants, between pemphigus and other vesicobullous disorders or between mucosal PV and other causes of oral ulceration is a diagnostic challenge. Direct immunofluorescence (DIF) shows a similar fluorescence pattern in PV and PF while indirect immunofluorescence carries the disadvantage of requiring animal substrates and shows substrate-dependent sensitivity, is a qualitative and subjective test and entails serial serum dilutions for its interpretation.…”
Section: Introduction Introductionmentioning
confidence: 99%